Exposure and mineralogical correlates of pulmonary fibrosis in chrysotile asbestos workers. Issue 8 (August 1997) - Green, F H; Harley, R; Vallyathan, V; Althouse, R; Fick, G; Dement, J; Mitha, R; Pooley, F
Abstract : OBJECTIVES: The relation between lifetime cumulative exposure to asbestos, pathological grade of pulmonary fibrosis, and lung burden of asbestos at death, was explored in a necropsy population of former workers in a chrysotile asbestos textile plant in South Carolina. METHODS: Estimates of cumulative, mean, and peak exposures to asbestos were available for 54 workers. Necropsy records and lung tissue samples were obtained from hospital files. Matched control cases were selected from consecutive necropsies performed at the same hospitals. The extent and severity of pulmonary fibrosis was graded on tissue sections. Mineral fibres in lung tissue were characterised by transmission electron microscopy combined with x ray spectroscopy. RESULTS: A significant positive correlation (r = 0.67, P < 0.0001) was found between lifetime cumulative exposure to asbestos and total lung burden of asbestos fibres. This relation was also found for the individual types of asbestos associated with the exposure: chrysotile and tremolite. Pulmonary fibrosis was correlated with both cumulative exposure to asbestos (r = 0.60, P < 0.01) and the concentration of asbestos fibres in the lung (r = 0.62, P < 0.0001). The concentration of tremolite fibres in the lung provided a better estimate of lung fibrosis than did the concentration of chrysotile. Asbestosis was usually present in asbestos textile workers with more than 20 fibre-years cumulative exposure. The lengths and aspect ratios of chrysotile asbestos, but not amphibole asbestos, were greater in the lungs of asbestos fibre workers than in the control population. Textile workers with lung cancer had significantly greater cumulative exposures and fibrosis scores than workers without lung cancer. CONCLUSIONS: Both cumulative exposure to asbestos and lung fibre burden are strongly correlated with severity of asbestosis. The data also support the hypothesis that the high prevalence of asbestosis and lung cancer in this population resulted from exposure to long fibres of chrysotile asbestos in the workplace.